Influence of concrete grade and level of seismicity on seismic design of reinforced concrete school building - Siti Najihah, Yaakup (2018)
In Malaysia, when there is natural disaster occur, reinforced concrete (RC) school building will be the main shelter for community to stay until the disaster dwindle. it is very important to make sure the design of RC school building in future can sustain the load from earthquake, which means it is important that RC school buildings to remain functioning even after gone through the earthquake. The objective of the study is to determine the effect of magnitude of Peak Ground Acceleration (PGA) and effect of grade of concrete on the amount of steel reinforcement. The model use for the study is two-storey RC school building which is design based on Eurocode 8. There are a total of six models with different value of PGA and grade concrete. Then, the analysis is conducted to all of the models by using Tekla Structural Designer to obtain both of the objectives. The information based on the amount of steel required is provided from the analysis. It is represented by using Design Response Spectrum graph and tabulated tables that contained information like bending moment. Based on the analysis conducted in this study, the RC school building with higher PGA required higher amount of steel reinforcement while higher grade concrete required lower amount of steel reinforcement.